An Inventory System with Time-Dependent Holding Cost and Demand Dynamics under a Generalized Trapezoidal Neutrosophic Framework - Bhavani, Gudivada Durga; Mahapatra, G.S.; Lee, Gyu M. (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
This study presents an inventory model that incorporates realistic demand factors such as price, time, reliability, and the influence of advertisements. The model allows shortages with full backlogging and considers permissible delays in payment. Deterioration is represented by a two-parameter Weibull distribution, while the holding cost is modeled as a function of both holding time and item reliability. Since inventory cost parameters are often imprecise, this uncertainty is addressed using Generalized Trapezoidal Neutrosophic Numbers (GTrNNs). To handle such imprecision, a novel de-neutrosophication technique is proposed. The payment structure considers two cases: when the credit period is less than or equal to the replenishment cycle time, and when it is greater. Optimal solutions are derived by taking the time at which the inventory level reaches zero as the decision variable. Numerical examples and sensitivity analyses are conducted to examine the impact of variations in key parameters on the optimal inventory policy.